Invasive black rats as the main prey species for native predators following fires in agricultural-forest landscapes of northern Patagonia - Hidalgo-Corrotea, C (Elsevier Inc., 2026)
Fires may facilitate the invasion of exotic rodents, with effects that propagate to upper trophic levels. In the Patagonian region, native predators facing habitat disturbances can change their prey consumption towards exotic prey species, but this predator trophic behavior has not been documented in areas affected by fires. In this study, we assessed the importance of exotic rodents in the diet of chilla foxes (Lycalopex griseus) and barn owls (Tyto furcata) living in an agricultural-forest landscape of northern Patagonia affected by a fire. In this landscape, the scats and pellets of chilla foxes and barn owls, respectively, were surveyed and used to analyze changes in the diet of these predators before and after the fire. The dietary breadth of these predators exhibited a temporal fire-induced decline. The exotic black rat (Rattus rattus) was the only prey whose consumption by barn owls and chilla foxes increased after the fire. After the fire, barn owls and chilla foxes reduced their relative consumption of native rodents and other prey when compared to the consumption of black rats. Our results indicate fires modify the dietary composition of native predators, from a diet based on native rodents to another dominated by exotic rodents. Black rats can compensate the loss of prey native to northern Patagonia, with barn owls and chilla foxes adjusting their diets to exotic prey availability after fires. However, the conservation implications of fires on native predators require a long-term evaluation. © 2026